A Variação Linguística no Novo Ensino Médio: análisecrítica do livro didático Linguagens em Interação à luzda Base Nacional Comum Curricular - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
This paper term aims to investigate the presence and treatment of Linguistic Variation in thePortuguese Language textbook “Language and Interaction”, from the New High School. Toachieve this purpose, a bibliographical review was carried out on the triad Language,Variation and Teaching, especially the writings of Bagno (2007), Calvet (2002), Travaglia(2005), Faraco (2007), Lacerda (2021) and Pena-Ferreira (2022), as well as the assessment oftwo official documents of Brazilian basic education, the National Common Curricular Basefor Secondary Education (2017) and the National Curricular Parameters for SecondaryEducation (2002), regarding Linguistic Variation and the Portuguese Language , and theanalysis of the aforementioned textbook. This is a bibliographical research, as defined bySeverino (2007). The methodology used involved choosing the theme and object of research,choosing the work to be analyzed, literature review and writing the text. The textbookinvestigated was found in a state public school, in the city of Santarém-PA, during thepedagogical internship period of the author of this text, started in November 2022 and is inforce to date. Data analysis was based on the script of questions about Portuguese languagedidactic works, proposed by Bagno (2007). Among the results obtained, the following standout: 1) the analyzed textbook addresses the phenomenon of Linguistic Variation in more thana chapter of the work advocates that this occurs at all levels of the language, but does notreflect the occurrence of Variation in all of them; 2) does not establish the difference betweenstandard norms and educated norms, highlighting the lexical level of the language as the mainspace of Variation and the regional factor as the main driver of this; 3) the textbook does notsufficiently reflect the Variation between speaking and writing, nor does it advance thegrammatical content, which is also variable. This work confirms the need to understandVariation as a basic phenomenon of Portuguese Language classes, and not just as an isolatedthematic element. The findings of this study contribute to the field of Literature, specificallywith regard to the Teaching of Portuguese Language in New High School, through didacticworks. Furthermore, there is a need for continued research in this area, which may be basedon this first research. This monograph, therefore, offers a necessary reflection on thephenomenon of Linguistic Variation in New High School, considering some theoreticalpostulates and official basic education documents, in view of deepening discussions about thisphenomenon in the classroom.
Keywords: Língua Portuguesa; Variação linguística; Ensino. Livro didático; NovoEnsino Médio; CNPQ:: LINGÜÍSTICA, LETRAS E ARTE